Observations on forensic linguistics - Sargsyan, Liana (Bulletin of Yerevan University B: Philology, 2021)
Forensic linguistics is a newly emerging field in Armenia. Developed and implemented in a practical environment, it has remained neglected in developing and implementing theoretical provisions, in the issues of methodology, training experts, and others. As an interdisciplinary phenomenon, it lacks a sufficient amount of elaboration; the structural and content features to perform an examination are not clearly described. The law poses some unsatisfactory requirements and criteria for an expert. Given the importance of the phenomenon, there is currently a need to develop and improve the field of linguistic expertise, in particular, to introduce a sound system for training linguistic experts.
Keywords: forensic linguistic examination; term issue; choice of expert, methodology; method; linguistic interpretation